Clemastine fumarate promotes myelin repair in a nonhuman primate model of demyelination characterized by absent spontaneous remyelination - Nadège Sarrazin; Rafik Arab; Christian Cordano; Elena Brazhnikova; Jérémy Chazot; Fabrice Arcizet; Corinne Bachelin; Dominique Langui; Daniel J. Bennett; Ahmed Abdelhak; Harkeerat Halait; Pierre Moissonnier; et al. (Proceedings of the National Academy of Sciences, 2026)
Promotion of remyelination has become a new therapeutic avenue, to prevent neuronal degeneration and promote recovery in white matter diseases such as multiple sclerosis. Clemastine fumarate among several promyelinating agents, has been validated as a promyelinating agent in rodents and has led to a first successful double-blind, placebo-controlled clinical trial evaluating a remyelinating therapy for multiple sclerosis (MS) [A. J. Green et al. , Lancet 390 , 2481–2489 (2017)]. To date, most of promyelinating strategies have been developed in short-lived rodent models of demyelination, which spontaneously repair. Well-defined nonhuman primate models closer to man would allow to efficiently advance therapeutic approaches, and namely to assess noninvasively, their efficacy in promoting functional repair. We developed a nonhuman primate model of optic nerve demyelination which leads to failed remyelination, progressive neuronal degeneration, and visual dysfunction, thus recapitulating several features of MS lesions and providing the missing link to translate emerging preclinical therapies to the clinic for myelin disorders such as multiple sclerosis [N. Sarrazin et al. , Proc. Natl. Acad. Sci. U.S.A. 119 , e2115973119 (2022)]. We used this model to assay the therapeutic benefits of clemastine. Our histological and ultrastructural findings show that clemastine is able to overcome the failed remyelination of the nonhuman primate optic nerve. We also used visual evoked potential, optical coherence tomography, and electroretinogram as noninvasive means to follow up the optic nerve de/remyelination process and correlated these findings with postmortem analysis to establish the safety and efficacy of clemastine therapy in promoting functional and morphological recovery in nonhuman primates. We demonstrate that clemastine can overcome chronic demyelination in nonhuman primates.